Leuconíquia i cultura popular - Veny, Joan (Caplletra. Revista Internacional de Filologia, 1999)
The materials from the «Atles Lingüístic del Domini Català» related to the names of «leuconíquia», or small white spots under people’s nails, a geolinguistic and anthropological study is performed of the various folk names «mentides, regals, alegries», etc.) as compared to other languages. The origin of such names is based on the belief that they represent different signs (that someone has been telling lies, that there is a forthcoming present, etc.) mostly developed in the world of children.